2021
DOI: 10.1097/spv.0000000000001065
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Characteristics, Evaluation, and Management of Women With Complaints of Recurrent Urinary Tract Infections

Abstract: Objective The aims of this study were to determine the proportion of women presenting for recurrent urinary tract infections (UTIs) who met the diagnostic criteria (culture-proven UTI ≥3 in 1 year or ≥2 in 6 months) and to assess advanced testing utilization, preventive therapy use, and risk factors. Methods This is a retrospective chart review of women seen as new urogynecology consults for recurrent UTI (rUTI) between April 1, 2017, and April 1, 2018,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 18 publications
2
4
0
Order By: Relevance
“…In line with other studies, we established that classic UTI symptoms are strongly associated with a UTI diagnosis [ 28 , 29 ]. Dysuria is the symptom with the highest risk of a UTI diagnosis in our study, which is in line with other reports and is part of the UTISA (UTI Symptoms Assessment questionnaire) score for UTIs [ 10 , 21 , 28 , 30 ]. Urinary retention is a well-known risk factor for UTI, which our data confirm even in the case of the symptom being present for less than fourteen days [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…In line with other studies, we established that classic UTI symptoms are strongly associated with a UTI diagnosis [ 28 , 29 ]. Dysuria is the symptom with the highest risk of a UTI diagnosis in our study, which is in line with other reports and is part of the UTISA (UTI Symptoms Assessment questionnaire) score for UTIs [ 10 , 21 , 28 , 30 ]. Urinary retention is a well-known risk factor for UTI, which our data confirm even in the case of the symptom being present for less than fourteen days [ 31 ].…”
Section: Discussionsupporting
confidence: 93%
“…The diagnostic yield of cystoscopy in female patients with rUTI in the literature varies from 0 to 7.6%, with cohort sizes ranging from 15 to 379. [20][21][22][23][24][25] Only 1.3% (6/467) of cystoscopies in this cohort demonstrated significant findings that altered management. It is important to point out that significant findings among all patients were exclusively in the cohort of patients with high-risk features/complicated rUTI.…”
Section: Discussionmentioning
confidence: 77%
“… 17 19 Recent studies examining women with rUTI undergoing cystoscopy by Pat et al ( n = 379), Dokubo et al ( n = 236), and Dieter et al ( n = 173) demonstrated diagnostic yields of 0.26%, 3.4%, and 2%, respectively, including findings such as calculi, diverticuli, fistulae, and bladder tumors. 20 22 Urologic societies consistently recommend reserving cystoscopy for patients with high-risk features and/or of advanced age, although these recommendations are based upon expert opinion and lack robust supporting evidence. 10 12 The EAU offers a “weak” recommendation to avoid cystoscopy in women without risk factors that are less than 40 years of age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To some extent, the ambiguity in the trial’s primary outcome is merely a reflection of the uncertainty about the optimal approach to diagnosing and initiating treatment for recurrent UTIs in the broader medical community. In routine practice, clinicians vary widely in their reliance on clinical tests to confirm episodes of recurrent UTIs, many patients are presumptively treated for recurrent UTIs when they do not meet conventional diagnostic criteria, and antibiotic overtreatment for both nonspecific symptoms and for asymptomatic bacteriuria is common. In contrast with routine care, women with preexisting chronic bladder syndromes were excluded from the trial by Hayward et al, decreasing the likelihood that participants were inappropriately suspected of having a recurrent UTI due to a mild or temporary flare in their chronic bladder symptoms.…”
mentioning
confidence: 99%